Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Gerai Fried Chicken X Kabupaten Tuban - Kristi Yoningsih; Kartika Wulandari; Afsah Indah Maulidah; Wijayanto Rahma Saldi (Jurnal Manajemen Agribisnis Terapan, 2026)
Fried chicken, characterized by its crispy flour coating, has become increasingly popular across various consumer groups and is widely accessible. One of the easily found fried chicken outlets in Tuban Regency is Fried Chicken X, which offers diverse menu options at relatively affordable prices. This study aims to analyze the influence of product quality, price, and service quality on customer satisfaction at the Fried Chicken X both partially and simultaneously. The research employed a quantitative approach by distributing questionnaires to consumers. The sample was determined using non-probability sampling with an incidental technique. The collected data, measured using a Likert scale, were transformed using the Method of Successive Interval (MSI) and analyzed through classical assumption tests and multiple linear regression using SPSS 26.0. The results indicate that product quality does not have a significant effect on customer satisfaction, as shown by a significance value of 0.193. Similarly, price does not significantly affect customer satisfaction, with a significance value of 0.394. In contrast, service quality has a significant positive effect on customer satisfaction, indicated by a significance value of 0.000. Simultaneously, product quality, price, and service quality have a significant influence on customer satisfaction at the Fried Chicken X. The coefficient of determination shows that these variables explain 61.7% of customer satisfaction, while the remaining 38.3% is influenced by other factors not examined in this study.